Water quality model-based methodology to assess assimilative capacity of wastewater discharges in rivers - F.M. Torres-Bejarano; M. Verbel-Escobar; M.C. Atencia-Osorio (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: One of the negative impacts of polluting activities on aquatic ecosystems is the loss of its natural self-purification ability, for this reason, the purpose of this research was to evaluate the Sinú river capacity to assimilate wastewater discharges.METHODS: Monitoring of several water quality parameters was carried out in the river at different seasons and a numerical method was used to simulate different scenarios through the Environmental Fluid Dynamics Code model. The model calibration process was tested applying the Root Mean Square Error and after calibrating the model, scenarios of increase and decrease of discharge concentrations and flows, and river flows were simulated. Finally, the results were compared to water quality reference limits.FINDINGS: Results show that the model accurately represented the real conditions of the studied river section for all the evaluated parameters. Also, assimilative capacity was affected mostly by the scenario in which the river flow was decreased by 50%, and the flows and discharges concentrations were increased five times; causing parameters such as ammonia nitrogen, chemical oxygen demand, phosphates, and total nitrogen, to exceed the established reference limits with maximum concentrations of 2.7 mg/L, 30.9mg/L, 0.98 mg/L and 6.3 mg/L; respectively. Higher concentrations of water quality parameters were mostly found in the dry season since lower velocities and river flows promote less pollutants mixing and dilution processes.CONCLUSION: The model spatiotemporal simulations showed the effect of the wastewater discharges on the Sinú River assimilative capacity and made it possible to find those scenarios where water quality parameters exceeded the reference limits, becoming an essential tool for water management and the development of strong water quality objectives by stakeholders and environmental authorities.